Advanced Concepts for Intelligent Vision Systems 12th International Conference, ACIVS 2010, Sydney, Australia, December 13-16, 2010, Proceedings, Part II - Blanc-Talon, Jacques; Bone, Don.; Philips, Wilfried; Popescu, Dan.; Scheunders, Paul.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 12th International Conference on Advanced Concepts for Intelligent Vision Systems, ACIVS 2010, held in Changchun, China, in August 2010. The 78 revised full papers presented were carefully reviewed and selected from 144 submissions. The papers are organized in topical sections on image processing and analysis; segmentation and edge detection; 3D and depth; algorithms and optimizations; video processing; surveillance and camera networks; machine vision; remote sensing; and recognition, classification and tracking.
Video Processing -- Video Quality Analysis for Concert Video Mashup Generation -- Speeding Up Structure from Motion on Large Scenes Using Parallelizable Partitions -- Mapping GOPS in an Improved DVC to H.264 Video Transcoder -- Scalable H.264 Wireless Video Transmission over MIMO-OFDM Channels -- A GPU-Accelerated Real-Time NLMeans Algorithm for Denoising Color Video Sequences -- An Efficient Mode Decision Algorithm for Combined Scalable Video Coding -- A Novel Rate Control Method for H.264/AVC Based on Frame Complexity and Importance -- Digital Image Tamper Detection Based on Multimodal Fusion of Residue Features -- Surveillance and Camera Networks -- Fire Detection in Color Images Using Markov Random Fields -- A Virtual Curtain for the Detection of Humans and Access Control -- A New System for Event Detection from Video Surveillance Sequences -- Evaluation of Human Detection Algorithms in Image Sequences -- Recognizing Objects in Smart Homes Based on Human Interaction -- Football Players Classification in a Multi-camera Environment -- SUNAR Surveillance Network Augmented by Retrieval -- Object Tracking over Multiple Uncalibrated Cameras Using Visual, Spatial and Temporal Similarities -- Machine Vision -- A Template Matching and Ellipse Modeling Approach to Detecting Lane Markers -- An Analysis of the Road Signs Classification Based on the Higher-Order Singular Value Decomposition of the Deformable Pattern Tensors -- An Effective Rigidity Constraint for Improving RANSAC in Homography Estimation -- Exploiting Neighbors for Faster Scanning Window Detection in Images -- Remote Sensing -- Optimisation-Based Image Grid Smoothing for SST Images -- Estimating 3D Polyhedral Building Models by Registering Aerial Images -- Content-Based Retrieval of Aurora Images Based on the Hierarchical Representation -- Improved Grouping and Noise Cancellation for Automatic Lossy Compression of AVIRIS Images -- New Saliency Point Detection and Evaluation Methods for Finding Structural Differences in Remote Sensing Images of Long Time-Span Samples -- Recognition, Classification and Tracking -- Regularized Kernel Locality Preserving Discriminant Analysis for Face Recognition -- An Appearance-Based Prior for Hand Tracking -- Image Recognition through Incremental Discriminative Common Vectors -- Dynamic Facial Expression Recognition Using Boosted Component-Based Spatiotemporal Features and Multi-classifier Fusion -- Gender Classification on Real-Life Faces -- Face Recognition Using Contourlet Transform and Multidirectional Illumination from a Computer Screen -- Shape and Texture Based Plant Leaf Classification -- A New Approach of GPU Accelerated Visual Tracking -- Recognizing Human Actions by Using Spatio-temporal Motion Descriptors.
Keywords: Computer science; Computer Communication Networks; Computer software; Artificial intelligence; Computer graphics; Computer vision; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Computer Graphics; Computer Communication Networks; Algorithm Analysis and Problem Complexity